2022
DOI: 10.1186/s12951-021-01222-7
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium iminofullerenes improve root growth of oxidative-stress maize through ASA-GSH cycle modulating redox homeostasis of roots and ROS-mediated root-hair elongation

Abstract: Background Various environmental factors are capable of oxidative stress to result in limiting plant development and agricultural production. Fullerene-based carbon nanomaterials can enable radical scavenging and positively regulate plant growth. Even so, to date, our knowledge about the mechanism of fullerene-based carbon nanomaterials on plant growth and response to oxidative stress is still unclear. Results 20 or 50 mg/L quaternary ammonium imin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…This effect is because H 2 O 2 treatment increases expression of genes related to root hair development, such as RBOHB and RBOHC, but IFQA decreases the accumulation of oxidative stress-related ROS and thus the activity of NADPH oxidase. 180 ROS results in AF bundling. The der1-3 mutant of ACTIN2 showed shorter, thinner AFs.…”
Section: Under Abiotic Stressmentioning
confidence: 98%
See 1 more Smart Citation
“…This effect is because H 2 O 2 treatment increases expression of genes related to root hair development, such as RBOHB and RBOHC, but IFQA decreases the accumulation of oxidative stress-related ROS and thus the activity of NADPH oxidase. 180 ROS results in AF bundling. The der1-3 mutant of ACTIN2 showed shorter, thinner AFs.…”
Section: Under Abiotic Stressmentioning
confidence: 98%
“…Exogenous H 2 O 2 inhibits root hair density and mean root hair length in Arabidopsis , but this inhibition is alleviated by application of exogenous quaternary ammonium iminofullerenes (IFQA). This effect is because H 2 O 2 treatment increases expression of genes related to root hair development, such as RBOHB and RBOHC , but IFQA decreases the accumulation of oxidative stress-related ROS and thus the activity of NADPH oxidase …”
Section: Root Hair Development and Adaptation Under Abiotic Stressmentioning
confidence: 99%
“…The influence of fullerene derivatives like other nanomaterials is defined by their sizes, composition of functional groups, concentration, and species differences in plant response and environmental conditions [1,19,20]. Positive effect of the specified compounds on plants is probably associated with antioxidant activity, in particular with capability of binding reactive oxygen intermediates as was clearly shown on the barley plant example [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that APX is the most important scavenging enzyme ensuring the scavenging capability of reactive oxygen species ( Czarnocka and Karpiński, 2018 ). Furthermore, it has been previously reported that for mitigating and enhancing stress tolerance AsA/DHA ratios are far more important than AsA contents ( Szalai et al., 2009 ; Yu et al., 2021 ; Tai et al., 2022 ). Current results revealed lower AsA/DHA as well as GSH/GSSG ratios in 3X watermelon as compared to 2X.…”
Section: Discussionmentioning
confidence: 99%